Measurement of earnings management before and after applying IFRSS using jones’ modified method an applied research in a sample of banks listed in the Iraqi stock exchange - Sabeha Barzan Farhood, Dr (International Journal of Accounting and Economics Studies, 2018)
In the year 2016, all commercial banks in Iraq were obliged to switch from the application of the local unified accounting system to the application of International Financial Reporting Standards (IFRSs) to improve the quality of accounting information and make it relevant for decision-making. The objective of the research is to measure earnings management in a number of banks which applied IFRSs at the end of the financial year 2016 through their application on a sample of banks for the years (2012-2013, 2014, 2015, 2016). The results were compared with the measurement of earnings management under the application of the unified accounting system (before the adoption of IFRSs) and after the application of the (IFRSs). The researcher concluded that the percentage of earnings management in the years in which the banks applied the unified accounting system is very close to its percentage in the case of the application of IFRSs, which shows that the application of IFRSs did not change the percentage of earnings management in banks. Â Â